Prevalence of Depression among Infertile Couples in Iran: A Meta-Analysis Study - Seyyedeh Zahra Masoumi; Jalal Poorolajal; Afsaneh Keramat; Seyyed Abbas Moosavi (Tehran University of Medical Sciences, 2013)
Background: Several studies have been conducted in Iran in order to investigate the prevalence of depression among infertile couples. However, there is a remarkable diversity among the results. This meta-analysis was conducted to estimate an overall prevalence rate of depression among infertile couples in Iran.Methods: International and national electronic databases were searched up to June 2011 including MEDLINE, Science Citation Index Expanded, Scopus, SID, MagIran, and IranMedex as well as conference databases. Furthermore, reference lists of articles were screened and the studies' authors were contacted for additional references. Cross-sectional studies addressing the prevalence of depression among infertile couples were included in this meta-analysis. We assessed 12 separate studies involving overall 2818 participants of which 1251 had depression.Results: Overall prevalence rate of depression among infertile couples was 0.47 (95% CI: 0.40, 0.55). The prevalence rate of depression was 0.44 (95% CI: 0.32, 0.56) during 2000 to 2005 and 0.50 (95% CI: 0.43, 0.57 during 2006 to 2011. The prevalence rate of depression was 0.46 (95% CI: 0.39, 0.53) among women and 0.47 (95% CI: 0.40, 0.54) among men.Conclusion: Not only the prevalence of depression in infertile couples was high but also had increasing growth in recent years. Furthermore, despite many studies conducted addressing the prevalence of depression in infertile couples, there is however a remarkable diversity between the results. Thus, one can hardly give a precise estimation of the prevalence rate of depression among infertile couples in Iran now.